Pembangkit Listrik tenaga Nuklir : Manfaat dan potensi bahayanya - MUHTADI, Fathoni; Sanyoto, Aris ; Setiawati, Asih; Firdausy, Carunia Mulya; Wilantara, Sam (2009)
VIII, 25 hlm.: ilus.; 21 cm ( 3eks)